2021
DOI: 10.1093/schizbullopen/sgab002
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Immune-Related Markers in Lymphocytes and Prefrontal Cortex in Schizophrenia

Abstract: Schizophrenia is a severe neuropsychiatric disorder associated with a wide array of transcriptomic and neurobiochemical changes. Genome-wide transcriptomic profiling conducted in postmortem brain have provided novel insights into the pathophysiology of this disorder, and identified biological processes including immune/inflammatory-related responses, metabolic, endocrine, and synaptic function. However, few studies have investigated whether similar changes are present in peripheral tissue. Here, we used RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The specific contribution mediated by the inflammation on the molecular features of the disease will be detailed in the following sections (Fig. 2) [44].…”
Section: Early Life Infections/inflammation In Schizophreniamentioning
confidence: 99%
“…The specific contribution mediated by the inflammation on the molecular features of the disease will be detailed in the following sections (Fig. 2) [44].…”
Section: Early Life Infections/inflammation In Schizophreniamentioning
confidence: 99%
“…In contrast to these previous studies, we used brain mRNA expression to subdivide the schizophrenics and not peripheral cytokine expression. However, there has been reported concordance between the expression levels of inflammation-related genes in the periphery and in the frontal cortex [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence that inflammation and the immune system may play a role in the schizophrenia pathophysiology (e.g., [ 20 , 21 , 22 , 23 , 24 ]). Building on that, multiple research groups have identified a “high inflammation” or “immuno-subtype” where a subset of schizophrenics show upregulated expressed in immune or inflammation related genes [ 7 , 9 , 10 , 11 , 12 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory biomarkers were assayed in plasma as a surrogate for measuring levels directly in cerebrospinal fluid and levels of peripheral biomarkers may not reflect levels of these biomarkers in the central nervous system (CNS). In support of using peripheral biomarker levels, one study reported that CNS changes in immune/inflammatory mRNA expression are reflected in similar mRNA expression changes in lymphocytes (Gatta et al, 2021). Selection of specific biomarkers and cognitive tests were based on available literature, and we may have overlooked additional important inflammatory biomarkers as well as cognitive domains.…”
Section: Limitationsmentioning
confidence: 99%